Strategic compensation : a human resource management approach - Martocchio, Joseph J. (Hoboken, NJ : Pearson Education, 2025)
'Strategic Compensation: A Human Resource Management Approach provides the foundation for building compensation systems in a variety of work organizations. The content of this textbook establishes the structure and design elements of compensation systems in a forward-looking framework that addresses decision making that supports companies' strategic plans. This approach, therefore, positions compensation practice as essential and compensation professionals as business partners. Individuals who pursue careers outside the compensation field will understand how to interact with compensation professionals for promoting effective recruitment, motivation, and retention of talent. This textbook is readable, with a conversational tone and clear explanations for concepts and practices. It conveys the relevance of compensation system design overall as well as individual topics for organizations and aspiring professionals; and, this textbook takes on contemporary topic coverage in every chapter'--
Part I setting the stage for strategic compensation -- Strategic compensation: a component of human resource systems -- Contextual influences on compensation practice -- Part II bases for pay -- Traditional bases for pay: seniority and merit -- Incentive pay -- Person-focused pay -- Part III designing compensation systems -- Building internally consistent compensation systems -- Building market-competitive compensation systems -- Building pay structures that recognize employee contributions -- Part IV employee benefits -- Discretionary benefits -- Legally required benefits -- Part V contemporary strategic compensation challenges -- Compensating executives -- Compensating the flexible workforce: contingent -- Workers, remote work, and flexible work schedule arrangements -- Part VI compensation issues around the world -- Compensating expatriates -- Pay and benefits outside the United States.
'Rental edition'--Cover.
Includes bibliographical references and index.
Keywords: Compensation management